Current challenges and threats of regional development, the ways to overcome them - Dzhyhora, Olha (Public Policy and Accounting, 2020)
The article is devoted to the study of challenges, the main threats to the development of regions and key ways to overcome them. The strengths and weaknesses, opportunities and threats of the regions have been studied with the help of SWOT-analysis. The interrelations of the regional development SWOT-matrix elements and variants of correlations among internal factors and external influences on the regions development have been determined. The use of graph-theoretic model for quantitative assessment of SWOT-matrix elements (strengths, weaknesses, opportunities, threats) has been proposed, as a result of which the priority opportunities have been identified, which implementation contributes to regional development: deepening integration with the EU, improving the business climate in Ukraine, stimulating the development of small and medium business.